Unity Is Strength: The Mutual Alliance between CFTR and SLC26A6 as Therapeutic Opportunity in Cystic Fibrosis - Marilena Pariano; Cinzia Antognelli; Luigina Romani; Claudio Costantini (Pharmaceuticals, 2024)
Patients with cystic fibrosis (PwCF) have recently experienced an unprecedented breakthrough with the adoption of modulator therapy in clinical practice. This remarkable achievement has led to the reconsideration of disease management as the increased life expectancy has gradually shifted the attention over a spectrum of extra-pulmonary manifestations that become prevalent in the aging population. It comes to be that complementary approaches that target patient co-morbidities are needed for the optimal clinical management of PwCF. A strategy would be to adjuvate the cystic fibrosis transmembrane conductance regulator (CFTR) in performing its functions in the different organs in which it is expressed. Solute carrier family 26 (SLC26) members appear ideal in this context. Indeed, they not only cooperate with CFTR in the organ-dependent regulation of ion fluxes but physically interact with it to reciprocally modulate their function. In this opinion, we summarize available evidence pointing to a physical and functional interaction between CFTR and SLC26 members, with a particular focus on SLC26A6 for its wider expression and broader anion selectivity, and then discuss how restoring the physical interaction between CFTR and SLC26A6 might be beneficial in the treatment of PwCF in the era of modulator therapy.